Hemophagocytic lymphohistiocytosis and visceral leishmaniasis in children: case report and systematic review of literature - Maria Scalzone; Antonio Ruggiero; Stefano Mastrangelo; Giovanna Trombatore; Vita Ridola; Palma Maurizi; Riccardo Riccardi (Journal of Infection in Developing Countries)
Hemophagocytic lymphohistiocytosis is a potentially fatal disorder resulting from excessive activation and non-malignant proliferation of T lymphocytes and macrophages. Neoplasms, autoimmune disorders and systemic infections can cause secondary hemophagocytic syndrome. The association of hemophagocytic syndrome and visceral leishmaniasis is rarely found in childhood.  We report a case of an infant affected by hemophagocytic lymphohistiocytosis secondary to visceral leishamniasis and describe all cases of hemophagocytic syndrome associated with visceral leishamniasis in childhood reported in literature, focusing on clinical manifestation, diagnosis and treatment.